Social, economic, and political events affect gender equity in China, Nepal, and Nicaragua: a matched, interrupted time-series study. Issue 1 (31st December 2020) - Nguyen, Tuan T.; Darnell, Ashley; Weissman, Amy; Frongillo, Edward A.; Mathisen, Roger; Lapping, Karin; Mastro, Timothy D.; Withers, Mellissa
ABSTRACT: Background : Progress in gender equity can improve health at the individual and country levels. Objectives : This study's objective was to analyze recent trends in gender equity and identify historical and contextual factors that contributed to changes in gender equity in three countries: China, Nepal, and Nicaragua. Methods : To assess gender equity trends, we used the Gender Gap Index (GGI) from the World Economic Forum's Global Gender Gap Report (2006–2017). The GGI incorporated data on economic participation, educational attainment, health, and political empowerment for almost 150 countries. We selected China, Nepal, and Nicaragua because of their major changes in GGI and diversity in geographical location and economic status. We reviewed major social, economic, and political events during 2006–2017, and identified key events in each country. We compared countries' GGI with matched controls average using interrupted time-series analysis. Results : Nepal and Nicaragua both had dramatic increases in GGI (improvement in equity), Nepal (β = 0.029; 95% CI: 0.003, 0.056) and Nicaragua (β = 0.035; 95% CI: 0.005, 0.065). This was strongly influenced by political empowerment, which likely impacted access to education and employment opportunities. Despite major economic growth and new policies to address gender inequities (e.g. the One-Child Policy), China saw a significant decline in GGI between 2010 and 2017 (β = −0.014; 95% CI: −0.024, −0.004), largely resulting from decreased gender equity in educational attainment, economic participation, and health/survival sub-indices. Conclusions : Key social, economic, and political events helped explain trends in countries' gender equity. Our study suggested that supportive social and political environments would play important roles in empowering women, which would advance human rights and promote health and well-being of individuals, households, communities, and countries.